Juridical Review of the Mechanism of Election of Heads Area in Area Special Yogyakarta ( Perspective Democracy and Historical ) - Kelik Endro Suryono; Vicki Dwi Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Indonesia is a democratic country, hence the constitution Indonesia in a manner fundamentals confess And ensure sovereignty on actually belongs to the people. This is stated in Article 1 paragraph (2) UUD 1945, that